CONTROLE DE POTÊNCIA EM MICRORREDES CA ISOLADAS COM AEROGERADORES E BANCOS DE BATERIAS DISTRIBUÍDOS - Matos, José Gomes de (2014)
This work proposes a new strategy to control the generated power in an alternating current autonomous microgrid that has distributed generators and battery banks. There are no restrictions regarding the type of generator to be connected, however in this particular study the effectiveness of the proposed strategy is analyzed by considering that the power source is a wind turbine coupled to a permanent magnet synchronous generator. The microgrid analyzed consists of at least one bidirectional electronic converter powered by a battery bank, which has the function of forming the microgrid; an electronic converter connected to a wind turbine generator, which operates as a power supplier to the microgrid; loads, and other peripheral systems of control and maneuver. The main objective of the proposed strategy is to maintain the terminal voltages of battery banks under control and below its upper limit, even when momentarily the power demanded by the loads connected to the microgrid is less than the power sources generation capacity. The proposed strategy controls the terminal voltage of the battery banks, controlling the power output that comes from the generators. This is done without the use of dump loads or any physical communication between the electronic converters connected to the battery banks and the electronic converters connected to the generators. A modified droop control technique, based on the grid frequency, is used to inform to the power generator electronic converters on the amount of energy they need to generate in order to maintain the state of charge of the battery banks below their limits. The work also presents the methodology to design and tuning the controllers of the associated variables of the generation system. This includes the voltage and frequency grid, the active and reactive power generated by the generators, the DC bus voltages in all electronic power converters and the terminal voltage of the battery banks. All controllers are designed in the discrete domain. A strategy to decouple the effects of the input disturbances is incorporated, into each controller. Special attention is given to the grid voltage controller due the fact that the effect of the load current disturbance is very significant for the grid power quality. Issues x related to the operation of the wind turbine on its maximum power point are also addressed in the control of the power electronic converter connected to the generator. The control strategy proposed in this study is validated through experimental results obtained using a microgrid prototype of 15 kW rated power.